2015
DOI: 10.5539/jas.v7n4p174
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Petroleum Hydrocarbons in a Tropical Ultisol Using Legume Plants and Organic Manure

Abstract: Global emphasis on food security and soil health should consider rehabilitation of degraded lands, especially where oil contamination limits the use of such lands. Three legume plants (Gliricidia sepium, Leucaena leucocephala and Calapoconium caerulean) alone or along with 0.5% (w/w) (equivalent of 10 tons ha -1 ) poultry manure, were used to treat the soil, in which the oil residuals were monitored for three years. Results showed that significantly high levels of residual total petroleum hydrocarbon content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
5
1
0
2
Order By: Relevance
“…This might have caused increase in OM content with a corresponding relationship in the positive correlation (r = 0.40; p<0.05) between the OM and THC supported by the physicochemical properties of the waste oil pollutant (Table 6). A similar higher degradation and removal of petroleum hydrocarbon in vegetated soils than non vegetated bulk soil has been reported by Merki et al (2005b), Wang et al (2010), Wang et al (2013), Udom and Nuga (2015) and Edwin-Wosu and Nkang, (2017a).The performance of P. pterocarpum could be attributed to its extensive root system, which could be represented in a positive correlation (r = 0.40; p<0.05) between the plant root and THC content of the soil and also in the activities of the detoxifying enzyme of the plant (Edwin-Wosu and Nkang, 2016). Initial concentration of THC in the polluted soil (Ci) = 3.97mg/g Table 5: The phytoremediation potency of the species in the waste oil polluted soil.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This might have caused increase in OM content with a corresponding relationship in the positive correlation (r = 0.40; p<0.05) between the OM and THC supported by the physicochemical properties of the waste oil pollutant (Table 6). A similar higher degradation and removal of petroleum hydrocarbon in vegetated soils than non vegetated bulk soil has been reported by Merki et al (2005b), Wang et al (2010), Wang et al (2013), Udom and Nuga (2015) and Edwin-Wosu and Nkang, (2017a).The performance of P. pterocarpum could be attributed to its extensive root system, which could be represented in a positive correlation (r = 0.40; p<0.05) between the plant root and THC content of the soil and also in the activities of the detoxifying enzyme of the plant (Edwin-Wosu and Nkang, 2016). Initial concentration of THC in the polluted soil (Ci) = 3.97mg/g Table 5: The phytoremediation potency of the species in the waste oil polluted soil.…”
Section: Discussionsupporting
confidence: 82%
“…This could be represented in the negative correlation (r = -0.50; p<0.05) between PD and infiltration rate; reflecting an increase in infiltration and decrease in THC as exemplified in the negative correlation (r = -0.24; p<0.05) between THC and PD. The impact of these species could corroborate the assertion that leguminous plants do improve the aggregate sizes of degraded soils due to improved changes in physico-chemical conditions (Wang et al, 2013;Udom and Nuga, 2015). This could also exemplified in the positive correlation (r = 0.25; p<0.05) between PD and sand;and (r = 0.15;p<0.05) between PD and silt; reaffirmed by the negative correlation (r = -0.42; p<0.05) between THC and sand and (r = -0.42; p<0.05) between THC and PD (Edwin-Wosu and Nkang, 2017a).…”
Section: Discussionsupporting
confidence: 52%
“…This was in tandem with the assertion that plant species through dense and highly ramified fibrous root system can enhance phytoremediation hence they can penetrate impermeable layers such as hydrocarbon pollution sites ((Edwin-Wosu and Nkang, 2017b). Similar study has revealed leguminous plant improvement of aggregate sizes of degraded soils due to improved changes in physicochemical condition (April et al, 2020;Edwin-Wosu and Nkang, 2019a;Udom and Nuga, 2015). A significant reduction in clay content across species treated soil when compared with the polluted condition was recorded.…”
Section: Discussionsupporting
confidence: 58%
“…En la tabla 3 se muestra que los valores de la biomasa de P. vulgaris a nivel de las raíces inoculadas con A. vinelandii y P. polymyxa indirectamente hicieron evidente la fitodegradacion del ARA en las raíces de la leguminosa 5,13,14,18 , además de que ambos géneros y especies bacterianas están reportadas como capaces de hidrolizar y eliminar hidrocarburos detectados en el ARA 10,14,20,22,24 , lo que llevo al consecuente decremento de la concentración de esta mezcla. Al respecto Udom & Nuga 25 reportaron que en suelo contaminado por mezclas de hidrocarburos, sembrado con P. vulgaris se observó que genera un sistema radical denso y abundante, que fue mejor con la actividad benéfica de A. vinelandii y P. polymyxa al mantener una eficaz absorción minerales 19,20,25 mediante la conversión de los exudados de raíces de P. vulgaris en fitohormonas 13,19,22, de esa manera mayor tolerancia al estrés causado por el ARA [14][15][16] , en consecuencia P. vulgaris generó una biomasa radical suficiente para la eliminación del ARA, que llevo a la recuperación del suelo, útil en la producción agricola 17,18,20,22 , lo que se evidenció al detectarse una concentración de ARA, inferior a la mayor aceptada por la NOM-138.…”
Section: Discussionunclassified
“…En la tabla 4, se presenta el enriquecimiento del suelo con la LC y el FEMI que favorecieron la siembra de las semillas de P. vulgaris potenciado con A. vinelandii y P. polymyxa, con lo cual a los primeros 19 días, en especial a los 24 después de la siembra a nivel de planta se observó un decremento de la concentración del ARA, en parte por la fitodegradacion que se reporta, realizan las raíces de leguminosas cuando se siembran en un suelo impactado por hidrocarburos, esta acción de eliminación del ARA puede ser mejorada mediante A. vinelandii y P. polymyxa que se reportan hidrolizan algunos aromáticos que existen en el ARA 9,14,23,25 . Por tanto al reducir en el suelo el ARA a un valor 1152 ppm, una concentración inferior a la máxima permisible de la NOM-138, apoyan la utilidad de inocular leguminosas con A. vinelandii y P. polymyxa para acelerar la relativa eficaz eliminación del ARA en la recuperación de ese suelo, con fines agrícolas o recreativos 12,15,18 .…”
Section: Discussionunclassified